Evaluation of diagnostic accuracy of 3-D endoanal ultrasound in perianal fistula in comparison with intraoperative findings - Ehsan Rahmanian; Mojgan Frootan; Fakhri Anaraki; Elahe Alimadadi; Mahsa Ramezanpoor (Journal of Coloproctology, 2018)
Objective: Perianal fistula is a common and debilitating disease. The definite treatment is surgery, identifying of primary and secondary tract, internal opening of fistula has important role in planning of surgical techniques. This study's goal was to determine the diagnostic accuracy of 3-D ultrasound in perianal fistula in comparison with intraoperative findings. Materials and methods: This study is a cross-sectional study. Adult patients (18–85 years old) with anal fistula have been selected. 3-D EUS was done for all patients by gastroenterologist. Then surgery was done. Check lists filled by endoscopist and surgeon was studied and data analysis was done. Results: The study examined 76 patients, in according to results for kappa coefficient there was a perfect agreement between 3-D ultrasound results and surgery in internal opening that was 96% (p < 0.001) and concordance was 0.974. In extension tract the agreement was 0.973 and concordance was 0.987 (p < 0.001). Conclusion: There was perfect agreement between 3-D ultrasound and surgical findings in internal opening, primary tract and trunk expansion. 3-D ultrasound shows a high diagnostic accuracy when compared with surgery to assessment of perianal fistula before surgery. Resumo: Objetivo: A fistula perianal é doença comum e debilitante. O tratamento definitivo é cirúrgico. A identificação dos tratos primário e secundário e de abertura interna da fístula desempenha papel importante no planejamento das técnicas cirúrgicas. O objetivo do presente estudo foi determinar a precisão diagnóstica da USE 3D em casos de fístula perianal, em comparação com os achados cirúrgicos. Materiais e métodos: Este é um estudo transversal. Foram selecionados pacientes adultos (18-85 anos) com fístula anal. Todos os pacientes foram examinados por USE 3D realizada por um gastroenterologista. Em seguida, procedeu-se à cirurgia. O endoscopista e o cirurgião estudaram as listas de verificação, com análise dos dados. Resultados: Nesse estudo foram examinados 76 pacientes. De acordo com os resultados para o coeficiente kappa, foi observada perfeita concordância entre os resultados da USE 3D e cirurgia para IO, de 96% (p < 0,001), com concordância de 0,974. Na extensão do trato a concordância foi 0,973 e concordância de 0,987 (p < 0,001). Conclusão: Foi observada concordância perfeita entre USE 3D e os achados cirúrgicos em abertura interna, trato primário e expansão do tronco. USE 3D demonstra elevada precisão diagnóstica, quando comparada com a cirurgia, para avaliação da fístula perianal antes da operação. Keywords: Anal fistula, Three dimensional endoscopic ultrasounds, Surgery, Palavras-chave: Fístula anal, Ultrassonografia endoscópica tridimensional, Cirurgia